Pengembangan Sumber Daya Manusia Melalui Penyusunan Grand Design - Setyawati, Novita; Dewi Sri Woelandari (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2025)
Human resource development for transportation officials becomes an ongoing project if the type and quantity of human resource needs to be met are not known, in accordance with organizational needs. Preparing transportation support human resources through various processes, including education, training, technical guidance, workshops, outreach, and other activities for each type of competency development need. In response, a reference or guideline for developing a Grand Design for Development is needed to achieve the goals/targets set in the context of welcoming a Golden Indonesia.This research employed qualitative methods with a SWOT analysis. The conclusions of this study include the importance of structural changes within the organization, increased training and development, and enhanced utilization of information technology. Furthermore, collaboration between relevant agencies and external stakeholders is crucial.